Gender aspect of placental cryoextract hepatotropic effect during coadministration with esomeprazole, clarithromycin and metronidazole - Кошурба, І.В.; Гладких, Ф.В. (Матеріали науково-практичної конференції з міжнародною участю «XІ наукова сесія інституту гастроентерології НАМН України. Новітні технології в теоретичній та клінічній гастроентерології»: тези доп. (м. Дніпро, 14–15 червня 2023 р.,). Гастроентерологія. 2023;57(2):90–91., 2023)
Currently, treatment regimens for eradicating Helicobacter pylori (H. pylori) infection typically involve a combination of bismuth drugs, proton pump inhibitors, and 2–3 antibacterial drugs selected from a list that includes amoxicillin, clarithromycin, metronidazole, tetracycline, levofloxacin, rifabutin, or furazolidone. The use of different combinations is necessary due to the increasing prevalence of antibiotic resistance in H. pylori strains. Furthermore, the indiscriminate use of antibacterial agents can elevate the risk of adverse drug reactions. Hepatotoxicity is a commonly observed side effect associated with antibacterial agents used for H. pylori treatment. Consequently, our attention has been drawn to placental cryoextract, a biotechnological drug with potential hepatoprotective properties. The purpose of the study: to investigate the gender-specific effects of placental cryoextract on hepatotropic action in a model of tetrachloromethane-induced hepatitis with underlying cirrhosis induced by ethanol and liver damage caused by antiulcer agents. Materials and methods. Research was conducted on 112 male and female rats. Tetrachloromethane hepatitis with background ethanol-induced liver cirrhosis was reproduced by injecting an oil solution of CCl4 in combination with a 5.0% ethanol solution for 45 days. Modulation of the content of sex hormones was achieved by surgical ovariectomy or testectomy. Results and discussion. Administration of esomeprazole, clarithromycin, and metronidazole in chronic liver damage in animals without changes in hormonal status led to a statistically significant (p=0.01) 27.6% increase in the level of bilirubin in homogenates of liver tissues in female rats (78.7±4.5 mmol/l) than in males. The greatest decrease in the content of bilirubin (41.7%, p<0.001) with the use of cryoextract of the placenta was noted in castrated female rats with simulated tetrachlormethone hepatitis with background ethanol-induced cirrhosis of the liver, which were injected with antiulcer agents. Conclusions. Administration of cryoextract of the placenta has a pronounced hepatoprotective effect in animals of both sexes. In male rats with no change in hormonal status with simulated liver injury and the administration of antiulcer drugs, placenta cryoextract therapy was more effective than in female rats, as indicated by a more than 1.6-fold decrease in the content of bilirubin in the liver homogenates of male rats (43.1%, p<0.001) than in females (27.4%, p<0.01).
Кошурба ІВ, Гладких ФВ. Gender aspect of placental cryoextract hepatotropic effect during coadministration with esomeprazole, clarithromycin and metronidazole. Матеріали науково-практичної конференції з міжнародною участю «XІ наукова сесія інституту гастроентерології НАМН України. Новітні технології в теоретичній та клінічній гастроентерології»: тези доп. (м. Дніпро, 14–15 червня 2023 р.,). Гастроентерологія. 2023;57(2):90–91. DOI: http://doi.org/10.5281/zenodo.8094522
Keywords: кріоекстракт плаценти